"Better explanations" in multiple sclerosis diagnostic workup: A 3-year longitudinal study. (28th May 2019) - Calabrese, Massimiliano; Gasperini, Claudio; Tortorella, Carla; Schiavi, Gianmarco; Frisullo, Giovanni; Ragonese, Paolo; Fantozzi, Roberta; Prosperini, Luca; Annovazzi, Pietro; Cordioli, Cinzia; Di Filippo, Massimiliano; Ferraro, Diana; et al.
Abstract : Background: The exclusion of other diseases that can mimic multiple sclerosis (MS) is the cornerstone of current diagnostic criteria. However, data on the frequency of MS mimics in real life are incomplete. Methods: A total of 695 patients presenting with symptoms suggestive of MS in any of the 22 RIREMS centers underwent a detailed diagnostic workup, including a brain and spinal cord MRI scan, CSF and blood examinations, and a 3-year clinical and radiologic follow-up. Findings: A total of 667 patients completed the study. Alternative diagnoses were formulated in 163 (24.4%) cases, the most frequent being nonspecific neurologic symptoms in association with atypical MRI lesions of suspected vascular origin (40 patients), migraine with atypical lesions (24 patients), and neuromyelitis optica (14 patients). MS was diagnosed in 401 (60.1%) patients according to the 2017 diagnostic criteria. The multivariate analysis revealed that the absence of CSF oligoclonal immunoglobulin G bands (IgG-OB) (odds ratio [OR] 18.113), the presence of atypical MRI lesions (OR 10.977), the absence of dissemination in space (DIS) of the lesions (OR 5.164), and normal visual evoked potentials (OR 3.550) were all independent predictors of an alternative diagnosis. Interpretation: This observational, unsponsored, real-life study, based on clinical practice, showed that diseases that mimicked MS were many, but more than 45% were represented by nonspecific neurologic symptoms with atypical MRI lesions of suspected vascular origin, migraine, and neuromyelitis optica. The absence of IgG-OB and DIS, the presence of atypical MRI lesions, and normal visual evoked potentials should be considered suggestive of an alternative disease and red flags for the misdiagnosis of MS.